Epithelioid hemangioma of penis mimicking malignancy: A rare case - Kishore, Manjari (Urol Ann, 2017)
Penile epithelioid hemangioma (EH) is a rare vascular neoplasm with no definite etiology. Herein, we report a case of EH of the penis in a 64-year-old man presenting with painless, bleeding mass on the glans penis. The patient underwent local excision, and on histopathological examination, a diagnosis of EH was made. Immunohistochemistry revealed positivity for CD31, smooth muscle antigen, and negative expression of cytokeratin. The present case highlights the importance of histopathology in conjunction with immunohistochemistry to reach a definitive diagnosis of this rare benign entity and differentiating it from the close malignant mimics, thereby avoiding aggressive management of the patients.